FDI - The Hijack of Indian Retail Market - Kamaladevi, B. (Indian Journal of Marketing, 2010)
Foreign Direct Investment (FDI) flows have increased substantially in the last two decades. This has been a result of the reduction of barriers to FDI, considerable improvements in transportation and communication technologies, and the direct policy measures implemented by many governments to attract FDI. These developments have motivated the appearance of a large number of empirical papers that test the expected benefits that FDI inflows are assumed to bring to the host countries. Based on the result of these studies, it is also possible to assess the economic benefits of the governmental incentives to attract multinational enterprises (MNEs). Increased FDI inflows to a country can create several economic effects. Among others, FDI can affect labour and capital markets, trade patterns and economic growth.